2019
DOI: 10.1177/2050157919878759
|View full text |Cite
|
Sign up to set email alerts
|

Mobile communication, social presence, and perceived security on public transport

Abstract: Mobile phones have become a ubiquitous phenomenon on public transport. However, little attention has been given to the effect of mobile communication on perceived security on public transport. This paper develops a model of social presence and perceived security in order to understand the widespread use of mobile phones on public transport as well as its effects. The first part of the model suggests a mediating role of social presence to understand how perceived security motivates mobile communication. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…(Figeac & Chaulet, 2018). Furthermore, Reichow and Friemel (2020) argued that perceived insecurity is more likely on public transportation, and users may utilize mobile technology to create a sense of social presence that dispels insecurity. The phone's status as a symbol of security, which was particularly relevant in the early days of mobile phone adoption (Aoki & Downes, 2003), may remain especially relevant in transit.…”
Section: Using Mobile Technology On-the-gomentioning
confidence: 99%
See 1 more Smart Citation
“…(Figeac & Chaulet, 2018). Furthermore, Reichow and Friemel (2020) argued that perceived insecurity is more likely on public transportation, and users may utilize mobile technology to create a sense of social presence that dispels insecurity. The phone's status as a symbol of security, which was particularly relevant in the early days of mobile phone adoption (Aoki & Downes, 2003), may remain especially relevant in transit.…”
Section: Using Mobile Technology On-the-gomentioning
confidence: 99%
“…An example regarding perceived security illustrates this dynamic relationship. Reichow and Friemel (2020) found that traveling on an underground train was associated with perceived insecurity, hypothesizing that travelers would use their mobile devices to increase perceptions of social presence in order to reduce such feelings of insecurity (e.g., texting; Luo et al, 2021). But this behavior feeds back to influence perceptions of the environment itself.…”
Section: Integrating Research On Mobility and Mobile Media On-the-gomentioning
confidence: 99%
“…Whereas mobile media contribute to the public health challenge of distracted driving (Panek et al, 2015), they also fundamentally affect how people behave in some public transportation settings (Figeac & Chaulet, 2018). Indeed, one article suggested that mobile media may affect how safe people feel during the ride (Reichow & Friemel, 2019), while another underlined how mobile devices can facilitate helping (or gawking) at accident scenes (Andersson & Sundin, 2021).…”
Section: Search Query Processmentioning
confidence: 99%
“…In terms of affect, usage of mobile technology is often driven by boredom, but perhaps more so while on-the-go due to the lack of available alternatives (Figeac & Chaulet, 2018). Furthermore, Reichow and Friemel (2020) argued that perceived insecurity is more likely on public transportation, and users may utilize mobile technology to create a sense of social presence that dispels insecurity. The phone's status as a symbol of security, which was particularly relevant in the early days of mobile phone adoption (Aoki & Downes, 2003), may remain especially relevant in transit.…”
Section: Using Mobile Technology On-the-gomentioning
confidence: 99%
“…An example regarding perceived security illustrates this dynamic relationship. Reichow and Friemel (2020) found that traveling on an underground train was associated with perceived insecurity, hypothesizing that travelers would use their mobile devices to increase perceptions of social presence in order to reduce such feelings of insecurity (e.g., texting; Luo et al, 2020). But this behavior feeds back to influence perceptions of the environment itself.…”
Section: Integrating Research On Mobility and Mobile Media On-the-gomentioning
confidence: 99%